Characteristics of pneumonia with negative chest radiography in cases confirmed by computed tomography - Takatoshi Kitazawa; Hisanao Yoshihara; Kazunori Seo; Yusuke Yoshino; Yasuo Ota (Greater Baltimore Medical Center, 2020)
Background Chest radiography is commonly used for diagnosing community-acquired pneumonia (CAP). Computed tomography (CT) is not routinely recommended for initial assessment of CAP patients but is more sensitive and more specific than chest radiography. Objectives To investigate characteristics of pneumonia with negative chest radiography in cases confirmed by CT. Methods We included patients diagnosed with CAP in the emergency department, and chest radiography and CT were performed and sputum cultures were collected. The CR- group was defined as patients for whom infiltration of pneumonia was detected only on CT. The CR+ group was defined as patients for whom infiltration was detected on both chest radiography and CT. Data were collected retrospectively from medical records. Results A total of 138 patients were included, with 58 patients in the CR- group and 80 patients in the CR+ group. Mean age was higher in the CR- group than in the CR+ group, and white blood cell counts and C-reactive protein (CRP) levels were lower in the CR- group than in the CR+ group (8.4 × 103/μL vs 12.4 × 103/μL, p = 0.01; 4.7 mg/dL vs 15.6 mg/dL, p < 0.001, respectively). Laterality of the infiltrated lungs differed between groups (right:left:bilateral = 14:30:14 vs 48:20:12, p = 0.006). Multivariate logistic analysis identified leukocytosis, elevated CRP levels (odds ratio (OR) 3.57, p = 0.003), laterality (OR 2.16, p = 0.006) as predictors of pneumonia in the CR- group. Conclusion In pneumonia with negative chest radiography in cases confirmed by CT, milder inflammation and infiltration in the left lung tended to be seen.